Информатизация интеграционных объединений в сельском хозяйстве (Путеводитель предпринимателя, 2020)
The basic tendencies of development of agriculture in Russia are considered, factors of instability of branch are allocated. Variants of integration of agricultural manufacturers are shown and the ways of their information for increase of efficiency of activity of manufacturers of agricultural production are offered.